ANALYSIS OF THE EFFECTIVENESS OF DIGITAL MARKETING STRATEGIES IN INCREASING INTEREST IN ENTERING SCHOOL AT HJ PRIMARY SCHOOL. ISRIATI BAITURRAHMAN 2 - Setyowati, Dewi; Fatkuroji, Fatkuroji (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to find out how digital marketing strategies increase interest in entering school at SD Hj. Isriati Baiturrahman 2. This research is qualitative in nature by describing data and facts comprehensively through words. In this research, the results were obtained that the digital marketing strategy in increasing interest in entering school at SD Hj Isriati Baiturrahman 2 was in the effective category. This effectiveness is seen based on the researchers' findings, namely: 1. In digital marketing, schools use a combination of platforms such as Instagram for visual content, YouTube for video documentation and live streaming, Facebook for visual archive storage, and the school website as an official information center. 2. The school has such innovative Islamic-based education, extracurricular programs, and a family-friendly approach. 3. Elementary School Hj. Isriati Baiturrahman 2 shows that digital marketing that is planned and oriented towards school values is able to increase visibility, build a positive image, and attract the interest of prospective new students more effectively.